Kajian Hukum Otonomi Daerah Terhadap Pemekaran Empat Provinsi Baru Di Papua - Khoyron Nasir, Tomi; Syahuri, Taufiqurrohman (Journal Evidence Of Law, 2023)
The expansion of new provinces in Papua has been carried out, signed, and stipulated by the Indonesian Minister of Home Affairs.as many as four provinces have been added to the order administrative division of provinces in Indonesia, including: Mountainous Papua Provines, Southwest Papua, South Papua, and Central Papua. With the implementation of four new provinces in Indonesia to balance economic equality in the Papua region and provide regional autonomy freedom which is respected for Papuans who wish to form new provinces on the Papua Island where the Papua region is still so very large that it is sufficient to meet the welfare and living needs of all Papuans what is in it. Therefore the Indonesian government has established a regional autonomy policy within the Papua region to expand the island of Papua from previous two provinces to six provinces. The research method used by author is normative juridical research which includes four main theories, namely region autonomy theory, legal sovereignty theory, state sovereignty theory, theological theory. The purpose of this research is to find out the impact obtained by residents and the causes of Papuan’s desire on the expansion of new provinces in its territory and to find out the implementation of regional autonomy legal for the four new provinces in Papua. In the future, we hope that expansion of new provinces in Papua can produce a sense of justice and realize share properity in Papua.